Exploration of Nafion for the Electric-Double-Layer Gating of Metal-Oxide Thin Film Transistors. (8th February 2021) - Mou, Peng-Lin; Huang, Wan-Qing; Yan, Feng-Jie; Wan, Xi; Shao, Feng
Abstract : Nafion is the most classic and also the mostly used proton exchange membrane material for polymer electrolyte fuel cells. It has excellent proton transport property and chemical-physical stability. Yet to the best knowledge of the authors, Nafion as the gate dielectric had not been reported for the low voltage electric-double-layer transistors that gated by ion-based dielectrics. It is the aim of this work to explore the behavior of Nafion as the gate dielectric in metal-oxide electric-double-layer transistors. The effects of pretreatment with H2 O2 and H2 SO4 on the film properties were characterized and the correlations with EDLT's static and transient characteristics were analyzed. The pretreatment process is proved to be effective in enhancing the performance of as prepared transistors. The H2 O2 + 3.5 M H2 SO4 treated devices showed gate voltage below 1.5 V, field-effect mobility up to 16.9 cm 2 V −1 s −1, on/off radio at the level of 10 4, small hysteresis and transient response time of within 10 ms. These results solidify our understanding in proton gated electric-double-layer transistors which is helpful in guiding the future developments.